PENERAPAN MODEL PROBLEM BASED INTRUCTIONS (PBI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 023 KERUBUNG JAYA KECAMATAN BATANG CENAKU - Siti Fatonah; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is the facts that occurred in the fourth SDN 023 Kerubung Jaya, who showed symptoms of the students did not master the material science lessons have been learned. The problem of this research is